35 Core Polarization-Maintaining Multi-core Fiber for High Power Operation - Khalil Yahia; Grimm Moritz; Klenke Arno; Bahri Mehran; Jauregui Cesar; Nold Johannes; Haarlammert Nicoletta; Schreiber Thomas; Limpert Jens (EPJ Web of Conferences, 2024)
This work presents a novel rod-type 35 core multi-core fiber design that is capable of overcoming the inherent lack of polarization maintenance in such structures. A polarization extinction ratio of 10.5dB is achieved.